Kenabian dan Hukum - Rubiyatmoko, Robertus (Jurnal Orientasi Baru, 2012)
Prophecy and the law are two things which are very closely related. A prophet’s mission, among others, is to make sure that the Law, which is the gift of God himself, is fully understood and observed by the Israelites. This is the main task of the prophets and also that of Jesus as well. This law of love in the Old Testament received its basic formulation in the Ten Commandments and the Torah. While in the New Testament, it is elaborated throughout the Bible. The teaching of the Bible then became the basis for the teaching of the Church and its tradition, as well as normatively defined in the Code of Canon Law. The Law is not intended to negate human freedom. Instead, it is created to protect it and to guarantee the rights and responsilibities of each member of the community. To support this purpose, the system of sanctions and due canonical process was applied in the life of the Church.